A case of Exophiala oligosperma successfully treated with voriconazole - Rimawi, Bassam H.; Rimawi, Ramzy H.; Mirdamadi, Meena; Steed, Lisa L.; Marchell, Richard; Sutton, Deanna A.; Thompson, Elizabeth H.; Wiederhold, Nathan P.; Lindner, Jonathan R.; Boger, M. Sean (My University, 2013)
Exophiala oligosperma is an uncommon pathogen associated with human infections, predominantly in immunocompromised hosts. Case reports of clinical infections related to E. oligosperma have been limited to 6 prior publications, all of which have shown limited susceptibility to conventional antifungal therapies, including amphotericin B, itraconazole, and fluconazole. We describe the first case of an E. oligosperma induced soft-tissue infection successfully treated with a 3-month course of voriconazole without persisting lesions.